Managing diabetes mellitus in a complex world: navigating the challenges of polypharmacy - Liapi, Charis (Pharmakeftiki, 2025)
Diabetes mellitus (DM) presents complex challenges for both patients and healthcare providers. DM can lead to a range of complications and often coexists with other comorbidities. The need to effectively manage these complications, coupled with the presence of comorbidities, contributes to polypharmacy in DM patients. Polypharmacy can increase the risk of adverse drug events and drug interactions. As most serious adverse effects of polypharmacy in DM patients arise from drug interactions, the importance of careful medication management is paramount. Physicians must consider individual patient factors and conduct thorough pharmacological assessments in order to prevent unwanted effects. Furthermore, medication errors are a significant concern, particularly in elderly diabetic patients who are often prescribed multiple drugs due to comorbidities. Adhering to the Beers Criteria as well as regular monitoring for drug-drug and drug-food interactions, side effects, and medication appropriateness is essential for the optimization of the treatment and the reduction of the risk of adverse events in DM patients.